GRASP: A Multitasking Tether - Rabouille, Catherine; Linstedt, Adam D. (Frontiers in Cell and Developmental Biology, 2016)
Originally identified as Golgi stacking factors in vitro, the Golgi reassembly stacking protein (GRASP) family has been shown to act as membrane tethers with multiple cellular roles. As an update to previous comprehensive reviews of the GRASP family (Vinke et al., 2011) (Giuliani et al., 2011;Jarvela and Linstedt, 2012), we outline here the latest findings concerning their diverse roles. New insights into the mechanics of GRASP-mediated tethering come from recent crystal structures. The models of how GRASP65 and GRASP55 tether membranes relate directly to their role in Golgi ribbon formation in mammalian cells and the unlinking of the ribbon at the onset of mitosis. However, it is also clear that GRASPs act outside the Golgi with roles at the ER and ER exit sites (ERES). Furthermore, the proteins of this family display other roles upon cellular stress, especially in mediating unconventional secretion of both transmembrane proteins (Golgi bypass) and cytoplasmic proteins (through secretory autophagosomes).